Lead bioremoval by Bacillus spp. Isolated from industrial wastewater (Baghdad Science Journal, 2011)
Four samples were collected from the wastewater of State Battery Manufacturing Company (SBMC); Babylon 2 factory in AL-Waziriya district, as triplicates. Physical and chemical measurements were carried out such as temperature, pH, Lead concentrations and their ranges were: (19.5-34.5) °C, (6.1-6.4) and (4.5-6.5) mg/L, respectively. Six dominant Bacillus spp. isolates were isolated from these samples; namely, Bacillus subtilis N1, Bacillus subtilis N2, Bacillus subtilis N3, Bacillus cereus N4, Bacillus cereus N5 , Bacillus cereus N6. These isolates were capable of removing Lead from aqueous solutions in a capacity reached 27.6 ± 1.4, 10.1 ± 1.7, 74.5 ± 0.7, 8.93 ± 2.8, 8.1 ± 3.5, 1.6± 0.7 mg/L, respectively. Whereas cell walls, extracted from the same isolates, were able to remove Pb with high efficiency reached 77.7 ± 0.3, 18.6 ± 1.2, 9.5 ± 0.7, 42.4 ± 6.3, 9.9 ± 0.9, 6.7 ± 2.1 mg/L, respectively. This study showed that there is high variation (P